ACUTE TOXICITY OF GENERIC AND IN VITRO REFERENCE TOXICAMOL USING THE ARTEMIA SALINE TOXICITY BIOINDICATOR LEACH - Lopes Carreiro de Alencar, Eduardo; Paula Guimarães Sá, Ana; Rego da Silva, Renato; do Nascimento Silva, Jurandy (Health and Society, 2024)
This study aims to analyze, through an experimental study with a quantitative and descriptive approach, the toxicity and identification of the 50% Lethal Concentration (LC50) of the reference and generic paracetamol drops, both commercially available and produced in Brazil, comparing them with each other. The lethality test was performed on Artemia salina according to the methodology described by Meyer (1982), with some modifications. When performing the toxicity test on Artemia salina, for generic paracetamol, the LC50 obtained after 24 hours was 998.3 ± 0.2μg/mL. The reference paracetamol presented LC50 of 612.2 ± 1.3μg/mL. Based on the analysis of this research, it was found that the reference paracetamol presented signs of toxicity in nauplii of the microcrustacean Artemia salina, presenting a LC50 ≤1000μg/mL. Generic paracetamol showed a LC50 ≤1000μg/mL with a range above 1000 ug/mL indicating non-toxicity for this sample.